Persepsi Keluarga Penerima Manfaat Program Keluarga Harapan Terhadap Pelaksanaan Program Keluarga Harapan di Kelurahan Sri Meranti Kecamatan Rumbai Kota Pekanbaru - Elpi Sahara; Rd. Siti Sofro Sidiq (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2025)
Family Hope Program is a program that distributes social and health support for residents in the poor category with rules that must be met. This program is used as a step in reducing poverty problems. This research was conducted in Sri Meranti Village, Rumbai District, Pekanbaru City. The purpose of this study was to determine the benefits of the Family Hope Program (PKH) for PKH beneficiaries in Sri Meranti Village, Rumbai District and the perceptions of beneficiaries towards the implementation of the Family Hope Program (PKH) in Sri Meranti Village, Rumbai District. The researcher used a descriptive quantitative research method. The population of this study were all beneficiaries of the family hope program in Sri Meranti Village, Rumbai District, Pekanbaru City, with a sample of 10% of the total population. Data collection was carried out through observation, questionnaires and documentation. The results of the study obtained were 1) PKH beneficiaries felt that PKH was beneficial for them in meeting their daily needs and the perception of beneficiaries towards the implementation of the family hope program in Sri Meranti Village was a positive perception